Prospects of red passion fruit seeds (Passiflora edulis Sims.) as a source of halal probiotics - Nurrosyidah, Iif Hanifa; Mertaniasih, Ni Made; Isnaeni, Isnaeni (Universitas Ahmad Dahlan, 2023)
Indonesia is the most biodiversity country in the world, with a majority Muslim population, so halal issues are a priority. Natural resources are abundant, especially the tropical fruit that Allah SWT bestowed with a wide variety. Red Passion fruit (Passiflora edulis Sims.) is one of the tropical fruits widely consumed because of its delicious taste, rich in vitamins, minerals, and other active ingredients. The research reported that probiotics of Bacillus spp. Isolated from the red passion fruit seeds was proven to inhibit pathogenic microbes. Extended Strain Beta-Lactamase and Methicillin Resistant Staphylococcus aureus. The isolates also showed the ability to increase gamma interferon levels in the peripheral blood mononuclear cells in adult TB patients. Halal critical points for products containing probiotics can derive from raw material sources, especially those from animals. The Red passion fruit is classified as a safe, halal category. The process of isolating probiotics from red passion fruit seeds using fermentation technology in De man Rogose Sharp media, using simple materials, tools, and steps that are guaranteed to be halal. The compatibility of two probiotic isolates is the potential to be developed into a probiotic consortium for health supplement preparations and therapeutic complements.